INFLAMMATORY MARKERS IN CHILDREN WITH CONGENITAL HEART DEFECTS: A COMPARATIVE ANALYSIS BY LEVEL OF IMMUNE ACTIVATION - Mammadova, L.V.; Sultanova, N.G.; Hasanov, A.G.; Suleymanli, A.A. (World of Medicine and Biology, 2025)
The purpose of the study was to assess the immune status and levels of inflammatory markers in children with congenital heart defects, taking into account the degree of immune activation. A comparative analysis was conducted between patients with high and low immune activation, as well as a control group of healthy children. The study included 80 patients with congenital heart defects and 20 healthy children. The investigated parameters included CD3, CD4, CD8, CD95, CD16/56, CD19, HLA-DR, interleukin-6, tumor necrosis factor-alpha, as well as indicators of cardiac remodeling. The obtained results make it possible to identify immune phenotypes associated with disease progression and may be used for patient stratification and the development of personalized therapeutic approaches.
Keywords: congenital heart defects; immune status; inflammation; apoptosis; CD3; CD4; CD95; interleukin-6; TNF-α